Prototipe Monitoring Lampu Jalan Otomatis Menggunakan Mikrokontroller ESP32 dan Api BOT Telegram - Yusril Athallah Muhammad Yazid; Rizqi Agung Permana (Jurnal Teknik Informatika, 2023)
Public street lighting is one of the most important things because it is related to the security and safety of road users, especially at night which requires good lighting. The lack of lighting on the street, can have a dangerous impact on the community. Along with the development of current technological advances, making changes to the security system and to reduce face-to-face contact in this Covid-19 era. Technology is very important in the need to get the right information, fast and accurate. Currently the development of the IoT (Internet of Things) system which is the result of technological developments has become an inseparable part of people's lives. The IoT system is a very flexible system because anything can be controlled via the internet. And also with this IoT system, it is hoped that it will minimize the occurrence of face-to-face dialogue that can result in the transmission of the covid-19 virus. Therefore, an IoT-based system was created that uses the ESP 32 microcontroller as the processing center for checking damaged street lights or Mafunction whose information is sent through the Application Programming Interface (API) to be forwarded to the recipient's BOT Telegram.